Kualitas Lingkungan Tambak Insentif Litapenaeus Vannamei Dalam Kaitannya Dengan Prevalensi Penyakit White Spot Syndrome Virus - Maimunah, Yunita; Kilawati, Yuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
Increasing number of vannamei shrimp (Litapenaeus vannamei) ponds are switching from traditional to intensive farming systems, the more impact resulting among other potential environmental pollution. Pollution of the environment can directly degrade water quality cultivation and facilitate access of pathogens to infect the host. In this study examines how the quality of the environment, population and genetic characteristics of shrimp that live in some intensive pond associated with a disease that often affects farmed shrimp is White Spot Syndrome Virus (WSSV). Acquisition and primary data collection is done by conducting interviews and direct observation in the measurement of water quality parameters of both physics and chemistry and morphology observation of shrimp as well as the ICP11 gene expression detection of WSSV disease in vannamei shrimp DNA in the laboratory.